The relationship between hemoglobin levels and exercise intensity among students of the faculty of medicine Pasundan University - Kuspriyanti, Niken Puspa; Fauzia, Shiva Rosita; Rachmadhiani, Ira Dewi (Science Midwifery, 2025)
Background: Hemoglobin (Hb) is an essential protein responsible for oxygen transport and plays an important role in maintaining physical and cognitive performance. Exercise intensity is often associated with changes in hemoglobin levels; however, evidence among medical students remains inconsistent. Academic demands may influence students’ physical activity patterns and, consequently, their hemoglobin status. Objective: This study aimed to analyze the relationship between exercise intensity and hemoglobin levels among medical students at the Faculty of Medicine, Pasundan University. Methods: This analytical observational study employed a cross-sectional design involving 112 medical students selected through purposive sampling. Exercise intensity was assessed using a structured questionnaire, and hemoglobin levels were measured using the EasyTouch® GCHb device. Data analysis included univariate analysis and Chi-Square tests to determine the association between exercise intensity and hemoglobin levels. Results: Most participants had normal hemoglobin levels (62.5% of females and 42.9% of males) and reported moderate exercise intensity (91.1% of females and 82.1% of males). Statistical analysis showed no significant relationship between exercise intensity and hemoglobin levels in females (p = 0.264) or males (p = 0.505). Conclusion: Exercise intensity was not significantly associated with hemoglobin levels among medical students. These findings suggest that hemoglobin status in this population may be more strongly influenced by other factors such as nutrition, hydration, stress, and sleep quality rather than exercise intensity alone.